COMPARATIVE ANALYSIS OF THE WORD-FORMATION PROCESS IN THE STUDYED LANGUAGES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
A hot topic in modern linguistics is the formation of new words. Naturally, this phenomenon is connected with the word-formation process. Most words, both in Russian and in French, are formed using the morphemic method. This is due to the fact that these languages, that is, both French and Russian, belong to the Indo-European language family, which were greatly influenced by Latin and Greek.The problems of word formation in French, as well as in Russian, can be approached from two points of view - historical and etymological (investigating the origin of words and the development of a particular word-formation method) and structural-semantic (revealing semantic content).The purpose of this study is to find the commonality of the word-formation system of the two languages. Show the presence of similar and distinctive properties in the word-formation system of the two languages under study.